El costo en un hospital pediátrico - Peña Gallo, Arelys; Rivalta del Sol, Digna; Díaz Machado, Otmara; Martínez Ravelo, Roberto (Revista Cubana de Pediatría, 2026)
Contribuir a mejorar la eficiencia económica de esta unidad.